2016
DOI: 10.1245/s10434-016-5303-3
|View full text |Cite
|
Sign up to set email alerts
|

Modified Appleby Procedure for Pancreatic Adenocarcinoma: Does Improved Neoadjuvant Therapy Warrant Such an Aggressive Approach?

Abstract: In light of improved neoadjuvant therapeutic regimens, the modified Appleby procedure is a feasible and safe treatment option for patients with LAPC involving the CA, with morbidity and mortality similar to patients undergoing classic DP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…Recent studies have underlined this approach in the context of the presently available efficient chemotherapy regimens . A US study matched seventeen patients undergoing DP‐CAR after neoadjuvant therapy, mostly performed by Folfirinox chemotherapy in a 3:1 ratio with 51 patients undergoing DP alone.…”
Section: Neoadjuvant Therapy In Borderline Resectable Pancreatic Cancermentioning
confidence: 99%
“…Recent studies have underlined this approach in the context of the presently available efficient chemotherapy regimens . A US study matched seventeen patients undergoing DP‐CAR after neoadjuvant therapy, mostly performed by Folfirinox chemotherapy in a 3:1 ratio with 51 patients undergoing DP alone.…”
Section: Neoadjuvant Therapy In Borderline Resectable Pancreatic Cancermentioning
confidence: 99%
“…Previous studies have shown that DP-CAR can be performed safely by experienced teams at high-volume pancreatic surgery centers. 8 , 14 , 18 , 35 Most importantly, DP-CAR offers a survival benefit to a selected group of patients with otherwise unresectable pancreatic cancer. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Patients achieved a median survival of 35 months with a 79% rate of R0 resections . Another matched analysis of 17 patients undergoing a modified Appleby at Johns Hopkins Hospital shows a median survival of 20 months . A Japanese series comparing 16 patient with distal pancreatectomy and celiac artery resection to 27 patients with distal pancreatectomy alone demonstrated higher rates of R1 resection in the group with arterial resection, and ensuing shorter survival.…”
Section: Surgical Treatment Of Borderline and Locally Advanced Pancrementioning
confidence: 99%